Redesign of the Galaxy Gym Tembung Logo as Brand Identity - Simatupang, Yosua; Atika, Juli (Jurnal Indonesia Sosial Sains, 2024)
Competition in the fitness centre industry is getting tighter. This encourages Galaxy Gym Tembung to improve its brand identity in order to compete with its competitors. One of the efforts made is to redesign the logo. Galaxy Gym Tembung which is located in the area of Jalan Moh. Yakub Lubis No.dsn 3, Bandar Khalipah, Percut Sei Tuan District, Deli Serdang Regency, East Medan District, which was established in 2019, is one of the fitness centres located in Tembung with its owner named Ridho Santoso. This research aims to improve the brand identity of Galaxy Gym Tembung as a fitness centre. This study uses a qualitative method with a case study approach. Data was collected through interviews, observations, and documentation. The results of the study show that the redesign of the Galaxy Gym Tembung logo has a positive effect on brand identity. The new logo is easier to recognize and remember, more effective in conveying the meaning and message of the brand, and gives a professional and modern impression. This research contributes to Galaxy Gym Tembung in improving brand identity. The results of this research can also be useful for other designers in designing effective logos to improve brand identity.